SYTUACJA USTROJOWO-PRAWNA WYODRĘBNIONYCH WOJSKOWYCH SŁUŻB SPECJALNYCH - Prusak, Feliks (Zeszyty Prawnicze, 2016)
THE LEGAL AND CONSTITUTIONAL STATUS OF PARTICULAR MILITARY SPECIAL SERVICES Summary The subject of this study is an account of all the special services in the Polish military, a description of their legal and constitutional status and the scope of their powers, and an account of the formula for their activities as prescribed by statutory law. A point of paramount significance which is often ignored is the verification of the existence of a military reconnaissance service in the Polish Armed Forces. Another important point is the confirmation that the military special services do not have the legal capacity to act as a party to criminal proceedings.